A brain-based model of language instruction: from theory to practice - Farzaneh Iranmanesh; Mehry Haddad Narafshan; Mohammad Golshan (Tabriz University of Medical Sciences, 2021)
Background: A recent trend in second language acquisition and learning has been oriented towards brain-based studies and its association with brain development and plasticity. There are currently unprecedented opportunities for contemporary understanding of the neurological basis of second language (L2) learning owing to recent advances in cognitive neuroscience. Brain functional and structural investigations have contributed remarkably to biological explanations of language acquisition in addition to behavioral explorations. Methods: This study used a meta-analysis of previous findings of functional neuroimaging studies to elucidate the neuroanatomy of language learning from a functional perspective. By synthesizing existing literature, brain activation areas associated with different language learning skills and their convergence and overlap with other areas of activation for other cognitive and motor skills are extracted to reveal consistent functional areas of the brain. The current study attempts to link psycholinguistic research and cognitive neuroscience in the mediation of L2 learning and teaching. This review paper begins with a theoretical view of brain structure and function and concludes with a practical model of brain-based language instruction, resulting in a deeper understanding of the field. Results: Organized, conjoining cognitive neuroscience findings and L2 acquisition and learning approaches provide an opportunity for collaboration in cross-disciplinary studies. They provide new insights into how our brain represents languages. This article reviews recent advancements in our understanding of the brain; structural and functional organization of the brain; the role the brain plays in emotion, cognition, and development; and its consequent implication in language instruction. In effect, taking neurocognitive findings into account may have potential in developing brain-based tasks for the benefit of second language instruction in educational settings. Based on the revealed structural and functional areas of the brain and their networks of connection and interaction, manipulating areas of demanded activity may be as efficient as doing physical exercise to strengthen muscles. Conclusion: Developing a systematic model of second language instruction compatible with brain functions and patterns can benefit the rate and proficiency of language learners, thus improving language teaching and learning outcomes. This paper will aid the quest for utilizing general information of brain functions and related methods in developing practical, efficient language instruction as well as enhancing interdisciplinary research studies in both language and cognitive neuroscience.